2014
DOI: 10.1182/blood-2013-04-497123
|View full text |Cite
|
Sign up to set email alerts
|

The effect of desmopressin on platelet function: a selective enhancement of procoagulant COAT platelets in patients with primary platelet function defects

Abstract: Key Points• DDAVP is the drug of choice for mild hemophilia A and von Willebrand disease and (by unclear mechanisms) for platelet function disorders.• In vivo DDAVP selectively and markedly enhances the ability to form procoagulant platelets by enhancing intracellular Na 1 and Ca 21 fluxes.is clinically efficacious in patients with mild platelet function disorders but it is not known which mechanisms mediate this effect. Our aim was to evaluate the impact of in vivo DDAVP administration in these patients. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 53 publications
5
94
1
3
Order By: Relevance
“…Therapy typically consists of infusing plasma derived VWF containing concentrates or desmopressin (aka DDVAP) during acute bleeding episodes [76]. DDAVP promotes hemostasis by increasing endogenous levels of VWF and FVIII [77], and by increasing platelet activation [78]. The number of PMPs and VWF-bound MPs increases significantly after DDAVP administration [79], in conjunction with increased VWF functional activity in plasma.…”
Section: Phenotypic Vs Functional Assays For Microparticle Analysismentioning
confidence: 99%
“…Therapy typically consists of infusing plasma derived VWF containing concentrates or desmopressin (aka DDVAP) during acute bleeding episodes [76]. DDAVP promotes hemostasis by increasing endogenous levels of VWF and FVIII [77], and by increasing platelet activation [78]. The number of PMPs and VWF-bound MPs increases significantly after DDAVP administration [79], in conjunction with increased VWF functional activity in plasma.…”
Section: Phenotypic Vs Functional Assays For Microparticle Analysismentioning
confidence: 99%
“…19,20 A recent study documented that DDAVP markedly enhances formation of procoagulant platelets. 21 Antifibrinolytic agents, such as aminocaproic acid and tranexamic acid, have shown benefit in reducing peri-and postoperative bleeding and decreasing the need for allogenic transfusions, particularly in human patients undergoing cardiac surgery. 22 They have also been administered to people with a variety of hemostatic disorders, including VWD and Glanzmann thrombasthenia, with a clinical assessment of decreased numbers of bleeding episodes when administered prophylactically.…”
Section: Discussionmentioning
confidence: 99%
“…29 Therefore, the mechanism underlying our main findings likely reflects the consequences of inadequate levels of the prothrombotic coated-platelet population in the setting of a hemorrhagic insult, such as SICH. Although support for this hypothesis is provided by both animal and human studies, 25,26 recent data from Coluci et al 30 may also open the possibility of targeted interventions aimed at alleviating this situation by increasing platelet procoagulant potential. These authors have shown for the first time that in vivo use of 1-deamino-8-D-arginine vasopressin (desmopressin) in patients with mild platelet-based bleeding diatheses markedly enhanced the ability to form coated-platelets.…”
Section: Strokementioning
confidence: 99%
“…These authors have shown for the first time that in vivo use of 1-deamino-8-D-arginine vasopressin (desmopressin) in patients with mild platelet-based bleeding diatheses markedly enhanced the ability to form coated-platelets. 30 As a result, future studies aimed at examining the potential role of desmopressin in patients with SICH identified by the lowest coated-platelet potential and the highest mortality risk may be warranted.…”
Section: Strokementioning
confidence: 99%